2013
DOI: 10.3126/jnps.v33i2.8314
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Estimation of Lead Content in Nepalese Traditional Ayurvedic Medicines Commonly Used in Children

Abstract: Introduction: Ayurvedic remedies are popularly used in practice for long time in Nepal. It is regarded as safe and free from side effects. However there are published reports of the high content of heavy metals like lead in such preparations. No such study has been done in Nepal looking at the lead content in ayurvedic preparations. The aim of this study was to detect the level of lead in commonly used ayurvedic remedies used in paediatric population if any. Materials and Methods: Seventeen samples were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…e permissible limit given by the Ayurvedic Pharmacopoeia of India [12] for lead is 10 ppm and cadmium is 0.30 ppm. Our study was found to be under the study conducted in Nepal by Ojha A et al, and none of the selected ayurvedic remedies contained a detectable amount of lead in parts per billion [28]. Another study on ayurvedic churna preparation [9] found that the lead and cadmium were all above the permissible limit.…”
Section: Discussionmentioning
confidence: 46%
“…e permissible limit given by the Ayurvedic Pharmacopoeia of India [12] for lead is 10 ppm and cadmium is 0.30 ppm. Our study was found to be under the study conducted in Nepal by Ojha A et al, and none of the selected ayurvedic remedies contained a detectable amount of lead in parts per billion [28]. Another study on ayurvedic churna preparation [9] found that the lead and cadmium were all above the permissible limit.…”
Section: Discussionmentioning
confidence: 46%